Making sense of 'Intersex' and 'DSD': how laypeople understand and use terminology. Issue 2 (3rd April 2018) - Lundberg, Tove; Hegarty, Peter; Roen, Katrina
ABSTRACT: Various umbrella terms refer to sex characteristics that do not fit typical binary notions of somatic sex. Key terms include Intersex, reclaimed by 1990s activists, and Disorders of Sex Development ( DSD ) used in medicine since 2006. Professionals across diverse disciplines express strong preferences for specific terms, making assumptions about what those terms do . Here, we draw on 10 focus group-interviews (41 participants without particular knowledge of Intersex/DSD), and semi-structured face-to-face interviews with 33 parents and 22 young people with personal experience of Intersex/DSD to examine how diverse laypeople understand and use these two umbrella terms and their alternatives. Most participants agreed that 'DSD' was problematic. Most young people and parents used 'descriptive explanations' of how the body looked or worked. Many parents and young people also found 'Intersex' problematic, whilst a majority of focus group participants did not. We conclude that as 'experts by experience', young people and their parents use language pragmatically and flexibly in everyday life to a degree that people unfamiliar with their experiences can easily underestimate. We further conclude that prescriptive discussions on terminology in this area may be needlessly constraining for people with such personal experience.